2015
DOI: 10.1111/nan.12147
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression signatures in motor neurone disease fibroblasts reveal dysregulation of metabolism, hypoxia‐response and RNA processing functions

Abstract: AimsAmyotrophic lateral sclerosis (ALS) and primary lateral sclerosis (PLS) are two syndromic variants within the motor neurone disease spectrum. As PLS and most ALS cases are sporadic (SALS), this limits the availability of cellular models for investigating pathogenic mechanisms and therapeutic targets. The aim of this study was to use gene expression profiling to evaluate fibroblasts as cellular models for SALS and PLS, to establish whether dysregulated biological processes recapitulate those seen in the cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
110
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(118 citation statements)
references
References 95 publications
2
110
0
Order By: Relevance
“…These miRNAs show the same trend in multiple sclerosis PBMCs, ALS mouse spinal cord, and human ALS monocytes (Butovsky et al, 2012; Koval et al, 2013b; Ma et al, 2014); however, a decrease in miR-142-5p levels was reported in ALS subject fibroblasts (Raman et al, 2014), indicating potential tissue-specific regulation. Interestingly, miR-155 and miR-142-5p are predicted to regulate UBQLN2 and RELN , respectively, genes down-regulated among our DEGs (Figueroa-Romero et al, 2012).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…These miRNAs show the same trend in multiple sclerosis PBMCs, ALS mouse spinal cord, and human ALS monocytes (Butovsky et al, 2012; Koval et al, 2013b; Ma et al, 2014); however, a decrease in miR-142-5p levels was reported in ALS subject fibroblasts (Raman et al, 2014), indicating potential tissue-specific regulation. Interestingly, miR-155 and miR-142-5p are predicted to regulate UBQLN2 and RELN , respectively, genes down-regulated among our DEGs (Figueroa-Romero et al, 2012).…”
Section: Discussionsupporting
confidence: 52%
“…Importantly, the association of EIF2C4/AGO4 is also of particular interest given its role as a member of the argonaute family of proteins, a component of the RISC in miRNA function (Modzelewski et al, 2012; Sasaki et al, 2003; Winter and Diederichs, 2011). Indeed, recent studies demonstrate that argonaute proteins contribute to miRNA processing and function and are dysregulated in ALS and Huntington’s disease (Raman et al, 2014; Savas et al, 2008; Tan et al, 2014), suggesting that miRNA biogenesis may be altered in neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%
“…155 and 170) and two patients (nos. 12 and 17), four iAstrocyte lines from the same samples, and four fibroblast lines from one of our previously published studies (22). We focused on cell-type-specific gene expression rather than pathology-related transcriptional changes and we found that iOligodendrocytes, iAstrocytes, and human fibroblasts identify three distinct cell populations that significantly differ in gene expression as shown by the principal component analysis (PCA) carried out using the software platform Qlucore (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, fibroblasts are gladly accessible and may hold potential for short-term, rapid diagnostic and prognostic plans. Several studies have examined pathologic features in fibroblasts from ALS patients [5759]. They showed that fibroblasts recapitulate some of the hallmark abnormalities in TDP-43 observed in neuronal cells [57] and reported findings of increased membrane potential and decreased mitochondrial content in ALS fibroblasts [58].…”
Section: Discussionmentioning
confidence: 99%
“…They showed that fibroblasts recapitulate some of the hallmark abnormalities in TDP-43 observed in neuronal cells [57] and reported findings of increased membrane potential and decreased mitochondrial content in ALS fibroblasts [58]. Additionally, gene expression profiling of fibroblasts from ALS demonstrated differential expression of genes related in RNA processing and the stress response, a noteworthy decrease in miRNA production, and a reduced response to hypoxia, suggesting that fibroblasts can act as cellular models for ALS [59]. …”
Section: Discussionmentioning
confidence: 99%